2007
DOI: 10.1080/02699930600562235
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological and subjective indices of emotion as a function of age and gender

Abstract: Old, middle-aged and young persons of both genders were presented with slides containing pictorial stimuli that varied in emotional content. Each picture was rated on three dimensions: (1) valence; (2) arousal; and (3) dominance, using a 25-point scale. Heart rate, skin conductance, and forehead and cheek EMG were recorded during each slide presentation. The old and middle-aged groups showed greatly attenuated psychophysiological responses, compared to the young group. However, the old and middle-aged subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
8
23
1
1
Order By: Relevance
“…This means that it is easier to recognize the physiological emotional reactions of young people than those of older people on the axis of Valence or Dominance. This finding can be explained and supported by several previous studies, which demonstrate that the magnitude of physiological changes related to emotions are much smaller for elderly subjects than for young subjects [15,16]. Moreover, the present study also explores the effect of gender and age combined on the recognition rates.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This means that it is easier to recognize the physiological emotional reactions of young people than those of older people on the axis of Valence or Dominance. This finding can be explained and supported by several previous studies, which demonstrate that the magnitude of physiological changes related to emotions are much smaller for elderly subjects than for young subjects [15,16]. Moreover, the present study also explores the effect of gender and age combined on the recognition rates.…”
Section: Discussionsupporting
confidence: 89%
“…The studies on brain activities demonstrated that females react more to negative pictures whereas male have greater activities when watching erotic pictures [13,14]. Further, several studies indicate that old subjects have lower physiological responses in terms of electromyography, skin conductance, heart rate changes and finger temperature [15,16]. However, fewer investigations are conducted on the effect of gender and age on the psychophysiological emotion classification [17,18,19].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Past studies examining age-related differences in facial expressiveness have found that young and older adults express similar patterns of facial responding to visual stimuli such as emotional scenes, objects or faces (Reminger et al, 2000; Smith et al, 2005; Bailey et al, 2009). However, older adults compared to younger adults may exhibit diminished reactivity in facial expressiveness (Smith et al, 2005; Burriss et al, 2007). The reduction of facial expressiveness in the elderly has been thought to be a possible consequence of general physiological losses in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Towards to a more integrative view of the neuronal mechanisms involved in emotional processing, physiological recordings of the autonomic nervous system due to emotional stimuli should also be considered. Therefore, another study used IAPS pictures during heart rate, skin conductance and electromyographic (EMG) recordings [27]. The participants were divided into three groups (old, middle-aged and young) according to their age.…”
Section: Figure 5 Skin Conductivity Results During Passive Viewing Ofmentioning
confidence: 99%